IDENTIFIKASI KEBUTUHAN ALAT PEMADAM API RINGAN DI RSP UNIVERSITAS BRAWIJAYA MALANG - Yoga Pradipta (Universitas Airlangga, 2016)
The hospital will have a high fire risk in case of fire because in accommodating a lot of patients. Extinguish the fire at the first event of a fire can use the fire extinguisher. The aim of this study was to evaluate the fire extinguisher installation planning. This research was an observational research with a descriptive analysis method. The primary data were collected with observation, interviewing and the secondary data were collected from PT Nindya Karya, Rumah Sakit Pendidikan Universitas Brawijaya Malang projects. The sample of study was selected using by purposive sampling. The variables in this study were building construction classification and fire risk, fire classification and fire extinguisher requirement. The data were analyzed using descriptive analysis. The results showed that Rumah Sakit Pendidikan Universitas Brawijaya Malang project’s were public buildings classification with a low risk fire accident. This building’s risk fire classification were A, B and C. Each floor required 9 pieces of fire extinguisher with CO2 and dry powder types. This research was concluded that the fire extinguisher needs was accordance with Permenakertrans No. 4, 1980. It’s suggested to use the terms and conditions of Permenakertrans No.4, 1980 about the installation and maintenance requirements in planning the installation fire extinguisher.Keywords: Portable Fire Extinguisher identification, hospital buildin